Implementation of School Literacy Movement through Reading Literacy Journals in Elementary School - Qodaria, Rizka Lailatul Qodaria; Rozie, Fachrur Rozie (Literasi Nusantara, 2026)
The School Literacy Movement (Gerakan Literasi Sekolah/GLS) is a national program designed to enhance students’ basic literacy skills, particularly reading, writing, and critical thinking. However, its implementation at the elementary school level has not always produced optimal outcomes. This study aims to analyze the implementation of reading literacy journals as part of the School Literacy Movement in a sixth-grade elementary school. A qualitative descriptive approach was employed, involving classroom observations, interviews with teachers and students, and documentation analysis. The findings indicate that the use of reading literacy journals contributes positively to students’ reading habits and reflective skills, yet several challenges persist, including inconsistent implementation, limited reading materials, and varying levels of student motivation. Despite these constraints, the literacy journal serves as an effective medium for monitoring students’ reading activities and encouraging reflective reading practices. The study concludes that strengthening teacher guidance, providing diverse reading resources, and ensuring consistent literacy routines are essential to optimize the effectiveness of literacy journals within the School Literacy Movement framework.